The Role of Numerical Simulation in Fire Door Testing and Certification - Fernandes, Margarida; Araújo, Ana Catarina; Silva, João; Rodrigues, Nelson; Teixeira, Senhorinha; Teixeira, José Carlos (EAI Endorsed Transactions on Digital Transformation of Industrial Processes, 2025)
Passive fire protection is indispensable when designing and constructing safer buildings, particularly in industrial and public facilities, where consequences of a fire can be catastrophic. Although their purpose is not to extinguishing a fire, passive fire protection aims to delay flame and smoke propagation, gaining valuable time to save lives and goods. Fire doors are amongst the most common protection devices, and they must undergo strict certification tests to ensure they meet fire resistant standards. Such tests are expensive and time consuming, often carried out at longer distances in specialized facilities. Computational tools could provide a cost effective alternative to direct the design towards a viable product. Thus, with the objective of assessing the effectiveness of computational tools in the certification processes, a numerical model of a single-leaf sandwich door was developed. The simulations were carried out in Ansys Mechanical, using a one-way coupling approach between transient thermal and transient structural analyses. A key aspect of the model is the temperature-dependent convective heat transfer coefficient on the unexposed face, which greatly influences the predicted temperature evolution. From the numerical results, one may infer the maximum temperature of the door, as well as its displacements at the upper and lower edges. Thus the numerical model highlights the potential of using this methodology by allowing not only the temperature evolution to be recorded throughout the test at specific positions of the assembly, according to the standards, but also the identification of potential gaps between the door and the frame, which is critical for fire and smoke containment. Future work includes conducting an experimental trial to validate the model and refine the heat transfer parameters for improved predictive accuracy.